2001
DOI: 10.1021/bi010252s
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure and Backbone Dynamics of the CC Chemokine Eotaxin-3,

Abstract: Eotaxin-3 is one of three related chemokines that specifically activate chemokine receptor CCR3. We report the 3D structure and backbone dynamics of eotaxin-3 determined by NMR spectroscopy. Eotaxin-3 is monomeric under the conditions in this study and consists of an unstructured N-terminus before the first two conserved cysteine residues, an irregularly structured N-loop following the second conserved cysteine, a single turn of 3(10)-helix, a three-stranded antiparallel beta-sheet, an alpha-helix, and an unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 61 publications
2
32
1
Order By: Relevance
“…These derived order parameters are sensitive to local motions on the ps-ns timescale. Overall, both proteins exhibit dynamic behavior typical of other chemokines (1,58,59,61), with an aperiodic flexible N-terminal segment encompassing the first 15 or so residues that are most important for chemokine receptor binding, as has been found for other CXC chemokines (12,42). This is followed by ordered regular secondary structure elements, with the loop between the first two ␤-strands showing some flexibility, and a flexible C-terminal segment past the ␣-helix.…”
Section: Discussionmentioning
confidence: 68%
“…These derived order parameters are sensitive to local motions on the ps-ns timescale. Overall, both proteins exhibit dynamic behavior typical of other chemokines (1,58,59,61), with an aperiodic flexible N-terminal segment encompassing the first 15 or so residues that are most important for chemokine receptor binding, as has been found for other CXC chemokines (12,42). This is followed by ordered regular secondary structure elements, with the loop between the first two ␤-strands showing some flexibility, and a flexible C-terminal segment past the ␣-helix.…”
Section: Discussionmentioning
confidence: 68%
“…We found that receptor-binding regions of all three chemokines are highly flexible, suggesting that they also undergo induced fit to the receptor during their binding events. [167][168][169] Increases in Flexibility Induced by Ligand Binding. Despite the conventional view of binding in terms of inducedfit interactions governed by enthalpy-entropy compensation, several dynamics studies have indicated regions of proteins whose flexibility actually increases upon ligand binding.…”
Section: Effects Of Ligand Bindingmentioning
confidence: 99%
“…Structural studies have been carried out on a number of chemokines [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], indicating a significant level of homology at the tertiary structure level across the whole chemokine family. The prominent feature in a typical chemokine structure (Fig.…”
Section: Chemokine Tertiary Structurementioning
confidence: 99%